IRRIGATION WATER QUALITY ASSESSMENT USING CROSS IN DUHOK GOVERNORATE, KURDISTAN REGION OF IRAQ: - HAMI, Sipal Mohammed Taher Yousif; Hassan, Khalida (Science Journal of University of Zakho, 2025)
This study was conducted in the Duhok Governorate, Kurdistan Region of Iraq. A total of eleven natural water samples were collected from different water sources, including Rivers, lakes, wells, and drainage canals. All samples were analyzed in triplicate to ensure accuracy and reproducibility. Electrical Conductivity (EC), pH, Bicarbonate (HCO₃⁻), major Cations: Calcium (Ca²⁺), magnesium (Mg²⁺), Sodium (Na⁺), and Potassium (K⁺) were determined. Sodium (Na) levels ranged from 0.075 to 34.883 mmolc L⁻¹, with Kashi exhibiting the highest concentration, while the lowest one was registered in the Khabur River 0.075 mmolc L⁻¹). Potassium (K) concentration was generally low across all samples, with a mean of 3.253 mmol/L. Khabur River had the lowest across all samples (0.055 mmolc L⁻¹). The highest was in Hishkarow (0.63 mmolc L⁻¹). Calcium levels vary widely from 1.05 to 5.4 mmolc L⁻¹, with Bedol River showing the highest Ca concentration. Magnesium levels were higher than Ca in some samples. Qasara well 2 had the highest magnesium (Mg) concentration (6.00 mmolc L⁻¹), while the lowest was determined in Bedol River (0.6 mmolc L⁻¹). The adjusted Ca concentrations ranged from 0.907 to 3.548 mmolc L⁻¹, with the highest value in Duhok Dam. Highest Kashi EC (4.290 dS. m⁻¹) indicates very high salinity, which may affect water usability for irrigation, in contrast to the lowest in Bedol River (0.406 dS. m⁻¹), which suggests good water quality with low dissolved salts. Sodium Adsorption Ratio (SAR) was the highest for Kashi (17.082), indicating a high risk of soil dispersion if used for irrigation; however, the lowest was (0.056) for Khabur River, suggesting no salinity hazard. CROSS values ranged from 0.091 to 18.368, and CROSS (using adj. Ca) ranged from 0.103 (Khabure River) to 24.341 in (Kashi). The results highlighted variation in all parameters, influencing the suitability of these water sources for irrigation. The best water source for agriculture is the Khabur River, which has the lowest Na, EC, and SAR values, making it the best choice. The worst water source is Kashi, which has extremely high sodium, EC, and SAR values, making it unsuitable for irrigation. Municipal and Dam water, generally moderate in all parameters, making them safer for multiple uses. In contrast, well water varies but tends to have higher magnesium levels